Rádio esportivo expandido: o departamento de esportes da Rádio Tabajara no aniversário de 85 anos da emissora - Oliveira, Iago Sarinho de (2023)
This dissertation approache the concepts of Expanded Radio (KISCHINHEVSKY, 2016), Hypermedia (LOPEZ, 2010) and Convergent (FERRARETTO, 2012) from a case study with participant observation on the sports department of Rádio Tabajara, a government- linked broadcaster. of Paraíba that, in 2022, completes 85 years of existence. To this end, theoretical dialogues are carried out with contemporary researchers on sports radio, in addition to the reconstruction of the historical path of radio in Brazil and, mainly, of national and Paraíba radio sports coverage. The objective is to understand how the experiences in convergence and mobility of sports radio in Tabajara take place, based on the analysis of the station's YouTube and WhatsApp. For this, documentary data, semi-structured interviews and oral history records are used. The research demonstrates, from the experiences with the sport in Tabajara, current processes of assimilation and incorporation of the changes experienced in the radio production routine, with quantitative and qualitative results obtained throughout the year 2022.